Pengaruh Harga Rokok terhadap Perilaku Konsumsi Rokok pada Mahasiswa di Jatinangor - Bayu Rizky Prasetyo; Estro Dariatno Sihaloho (Universitas Batanghari Jambi, 2020)
Indonesia bears a huge burden on health problems arising from cigarette consumption. Many policies have been made by the government in order to control national cigarette consumption. One way is to increase the price of cigarettes. This research was conducted to determine the effect of cigarette prices with the income of student allowances on cigarette consumption. The research method used in this study is multiple linear regression. The data used in this study are primary data obtained using a survey in Jatinangor. Data collection techniques used in this study were random sampling, with a total of 60 students respondent. Data Characteristics of respondents in this study include cigarette prices, monthly allowance income and the number of cigarette consumption per month of students who live in Jatinangor. Based on the results of multiple linear regression analysis, it is found that the price of cigarettes and student allowance income has a positive and significant effect on cigarette consumption. This result can be a recommendation for the government that an increase in cigarette prices cannot significantly reduce cigarette consumption. The government can issue a smoking ban that is more effective in controlling the consumption of cigarettes to students.